Does the irrigated mango cultivation in the semiarid change the Physical and chemical attributes of the soil? - Santos, Leane Rodrigues dos; Lima, Augusto Miguel Nascimento; Rodrigues, Marcos Sales; Cunha, Jailson Cavalcante; Santos, Laura Paula Araújo dos; Soares, Emanuelle Mercês Barros; Silva, Adriano Victor Lopes da; Souza, Isadora Mororó de (Comunicata Scientiae, 2019)
The replacement of native vegetation by crops may result in changes in the chemical and physical attributes of the soil, preventing the sustainability of the agricultural production. Therefore, the aim of this study was to evaluate, in two consecutive years (2014 and 2015), the effect of irrigated mango cultivation in some physical and chemical attributes of the soil in relation to Caatinga in Petrolina-PE, Brazil. In areas under irrigated mango (under the canopy region and the row spacing) and Caatinga (taken as reference), soil samples were collected at the 0-10 and 10-20 cm depths. The chemical and physical analyzes were performed, and were calculated bases sum (BS), cations exchangeable capacity (CEC) and base saturation (V, %). The irrigate mango cultivation (canopy region) increased the macronutrients content (P, K, Ca and Mg), BS and V (%) for both evaluated years at the 0-10 and 10-20 cm depths. In soil under irrigated mango cultivation (under the canopy region and in the row spacing), the macronutrient contents presented a stochastic pattern in the years of 2014 and 2015. The change of land use, from Caatinga to irrigated mango cultivation, does not induce a negative impact in the soil chemical attributes under the adopted management conditions.